Impact of nutritional and educational support on home enteral nutrition - Adela Madrid-Paredes; Socorro Leyva-Martínez; Verónica Ávila-Rubio; Juan Bautista Molina-Soria; Patricia Sorribes-Carrera; Carmen Yeste-Doblas; José Antonio López-Medina; Victoria Eugenia Luna-López; María Luisa Fernández-Soto (BMC, 2023)
Abstract Background Home Enteral Nutrition (HEN) is used to prevent or correct malnutrition in outpatients. Due to the complexity of this process, the indication, follow-up, and results of an educational program of HEN patients was evaluated. Methods A prospective, observational, real-life, multicenter study was performed in 21 Spanish Hospital. Patients receiving HEN by nasogastric tube or ostomy were included. The following variables were collected: age, gender, HEN indication, type of formula, nutritional requirements, laboratory variables, complications, and quality standards of the educational program. To calculate the energy and protein requirements, the FAO/WHO/UNU formula was used considering the adjusted weight of the patients. All data were analyzed using SPSS.24. Results 414 patients were included. Most conditions diagnosed were neurodegenerative diseases (64.8%). 100 (25.3%) were diabetic. The mean weight was 59.3 ± 10.4 kg and BMI 22.6 ± 3.2. Moderate protein-calorie malnutrition was predominant at baseline (46.4%). Improvement in nutritional status at six months was recorded in more than 75% of patients (p < 0.05). Tolerance problems, diarrhea and abdominal distension fell between the 3- and 6-month visits (p < 0.05). Patients who received intermittent EN had fewer tolerance-related effects (OR 0.042; 95% CI 0.006-0.279) and less diarrhoea (OR 0.042; 95% CI 0.006-0.279). At the baseline and 6-month visits, compliance with the educational measures proposed by the prescriber was ≥ 99%. Conclusion The nutritional assessment to prescribe individualized HEN to each patient, together with educational measures and training in the proper use of this treatment for both patients and trainers, improves nutritional status and reduces the onset of adverse events.